Интравитреален антиангиоген третман на макуларен едем заради ретинални венски оклузии - Ивановска Аџиевска, Билјана (Медицински факултет, УКИМ, Скопје, 2017)
Aim: To evaluate the one-year efficacy and safety of intravitreal bevacizumab in the treatment of macular edema due to retinal vein occlusions. Methods: Interventional, prospective study of patients with macular edema due to central or branch retinal vein occlusion (CRVO or BRVO), followed for 12 months. Treatment-naïve patients with reduced best-corrected visual acuity (BCVA) and central macular thickness (CMT) of at least 250 microns received intravitreal injection of bevacizumab. After 1 month BCVA and OCT macula images were recorded. In patients with less than 30% improvement in BCVA and CMT 2 more injections were applied at 1.5-month intervals. In all other patients further injections were applied as needed. In cases with ischemic areas of retina, laser photocoagulation of the retina was performed. Results: 33 eyes with CRVO and 55 eyes with BRVO were treated. After 1 year 65 eyes (73.86%) had clinically significant improvement of BCVA (>0.3 logMAR units) with average number of injections of 1.98. Improvement of mean BCVA in CRVO was significant (p=0.001), from baseline 1.2±0.95 logMAR to 0.75±0.6 at 1-year. Significant improvement of mean BCVA (p<0.001) was also found in BRVO, from baseline 0.71±0.75 to 0.28±0.5 at 1 year. Baseline CMT was 852.21±298.20 μm for CRVO and 597.95±185.63 μm for BRVO. In both groups there was significant decrease (p<0.001) in CMT after 1 year of treatment. Panretinal laser photocoagulation was done in 75.8% of all eyes with CRVO and sectoral in 49.1% of eyes with BRVO. Conclusion: In macular edema due to RVO, intravitreal anti-angiogenic treatment provides sustained improvement in visual acuity and macular edema reduction within high percentage of treated eyes after 1 year of follow-up.
Intravitreal anti-angiogenic treatment of macular edema in retinal vein occlusions
Докторска дисертација одбранета во 2017 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Весна Димовска Јорданова.
Keywords: macular edema, retinal vein occlusion, bevacizumab, intravitreal injection